Pathogenic mutations in ARX, CDKL5 and STXBP1 genes are not associated with the early-onset epileptic encephalopathy in Malaysian pediatric patients: A pilot study - Jaafar, Ameerah; Alsiddiq, Feizel; Ling, King Hwa (Neuroscience Research Notes, 2018)
Gene mutation is one of the etiologies of early-onset epileptic encephalopathy (EOEE), an age-dependent seizure in infants, which leads to brain defects. Previous studies have shown that several genes namely, aristaless related homeobox (ARX), cyclin dependent kinase like 5 (CDKL5) and syntaxin binding protein 1 (STXBP1) are responsible for the pathophysiology of the syndrome. The study involved 20 EOEE patients and 60 control subjects, which aimed to investigate the clinical association of Malaysian EOEE subjects with 13 known pathogenic mutations in the genes of interest. In addition, the entire ARX exonic region was also sequenced for known and novel mutations. PCR specificity and efficiency were optimized using conventional PCR and High Resolution Melting Analysis (HRMA). All cases and approximately 10% of control amplicon samples were purified and subjected to DNA sequencing. All known mutations reported previously were not found in control subjects and Malaysian EOEE patients with 100% confirmation by sequencing results. Sequencing of ARX exonic regions of patient samples did not find any mutation in all exons. The preliminary study indicates that selected known pathogenic mutations of ARX, CDKL5 and STXBP1 are not associated with EOEE in Malaysian paediatric patients.